Implementasi Metode MAUT Dan AHP Dalam Penentuan Penerima Bantuan Program Indonesia Pintar (Studi Kasus: SD Aek Nabara Tonga) - Diffri Solihin Siregar; Billy Hendrik (Jurnal Penelitian Teknologi Informasi dan Sains, 2023)
The Smart Indonesia Program (PIP) is material assistance given to children aged 6-21 years for educational purposes. Provision of PIP assistance funds that are not on target is a problem that is currently happening at SD N 1109 Aek Nabara Tonga. The aim of this research is to identify students who are eligible and eligible for PIP assistance. To deal with this problem the author uses the Multi Attribute Utility Theory (MAUT) and Analytical Hierarchy Process (AHP) methods to get students who are eligible to receive PIP assistance. The criteria used in selecting PIP recipient students were PKH card owners, SKTM, orphans, report cards, and parents' income. The final results of the AHP and MAUT calculations, the student who gets the highest result is Riski Pinaldi Nasution with a final score of 0.982 and is a student who is eligible to receive PIP assistance, while the student with the lowest result is Muhammad Akbar Soleh with a value of 0.101 is a student who is not eligible to receive PIP assistance.